Deletion of delta-like 1 homologue accelerates fibroblast–myofibroblast differentiation and induces myocardial fibrosis. (13th April 2018) - Rodriguez, Patricia; Sassi, Yassine; Troncone, Luca; Benard, Ludovic; Ishikawa, Kiyotake; Gordon, Ronald E; Lamas, Santiago; Laborda, Jorge; Hajjar, Roger J; Lebeche, Djamel
Abstract: Aims: Myocardial fibrosis is associated with profound changes in ventricular architecture and geometry, resulting in diminished cardiac function. There is currently no information on the role of the delta-like homologue 1 ( Dlk1 ) in the regulation of the fibrotic response. Here, we investigated whether Dlk1 is involved in cardiac fibroblast-to-myofibroblast differentiation and regulates myocardial fibrosis and explored the molecular mechanism underpinning its effects in this process. Methods and results: Using Dlk1 -knockout mice and adenoviral gene delivery, we demonstrate that overexpression of Dlk1 in cardio-fibroblasts resulted in inhibition of fibroblast proliferation and differentiation into myofibroblasts. This process is mediated by TGF-β1 signalling, since isolated fibroblasts lacking Dlk1 exhibited a higher activation of the TGF-β1/Smad-3 pathway at baseline, leading to an earlier acquisition of a myofibroblast phenotype. Likewise, Dlk1 -null mice displayed increased TGF-β1/Smad3 cardiac activity, resulting in infiltration/accumulation of myofibroblasts, induction and deposition of extra-domain A-fibronectin isoform and collagen, and activation of pro-fibrotic markers. Furthermore, these profibrotic events were associated with disrupted myofibril integrity, myocyte hypertrophy, and cardiac dysfunction. Interestingly, Dlk1 expression was down-regulated in ischaemic human and porcine heart tissues. Mechanistically, miR-370 mediated Dlk1's regulation of cardiac fibroblast–myofibroblast differentiation by directly targeting TGFβ-R2/Smad-3 signalling, while the Dlk1 canonical target, Notch pathway, does not seem to play a role in this process. Conclusion: These findings are the first to demonstrate an inhibitory role of Dlk1 of cardiac fibroblast-to-myofibroblast differentiation by interfering with TGFβ/Smad-3 signalling in the myocardium. Given the deleterious effects of continuous activation of this pathway, we propose Dlk1 as a new potential candidate for therapy in cases where aberrant TGFβ signalling leads to chronic fibrosis.